Pengaruh Earning Per Share Dan Dividen Per Share Terhadap Harga Saham Perusahaan Pertambangan Yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022 - Lailatus Sa’adah; Silviana Najuwah (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2023)
The purpose of this study was to find out how the relationship between the ratio of earnings per share and dividends per share on the company's stock price. The subjects used in this study are mining sector companies listed on the Indonesian stock exchange in 2018-2022. The sampling technique in this study used a purposive sampling technique, using certain criteria and obtained a sample of 5 companies. The data processing technique used in this study uses multiple regression analysis assisted by Microsoft Excel 2013 and the Eviws 12 application. The implications of this study indicate that the ratio of earnings per share has an effect but not significant on stock prices, while dividends per share have an effect and are significant on prices. shares and simultaneously these two variables have no effect on stock prices. The suggestion in this study is that it is necessary to increase the company's financial performance in order to increase the company's profits so that the company's price can also increase.